2017
DOI: 10.1007/s13744-017-0508-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the Plant Surface Prior to Feeding and Oviposition: Differences in External Ultrastructure and Function Among Tarsi of Heliconius erato

Abstract: Adult foretarsi of Heliconius erato Linnaeus (Lepidoptera, Nymphalidae) are reduced in size and are not used for walking. Foretarsi of the female have specialized sensilla that are presumably used to identify the host plant, by drumming. The mid- and hind tarsi also bear sensilla in both sexes, but these have not been described in detail, nor has their chemosensory function been determined. We described and compared the tarsi of H. erato under light and scanning electron microscopy. Behavioral experiments show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 35 publications
5
13
0
Order By: Relevance
“…The morphology and the types of ovipositorial and tarsal sensilla found in this study are quite similar to those reported previously by (Cruz & Eizaguirre 2016) in Sesamia nonagrioides, Papilio hospiton (Sollai et al 2010) and Heliconius erato (Silva et al 2017). In our study, we focus on the ovipositorial and tarsal sensilla most likely involved in selection of a suitable host for oviposition.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The morphology and the types of ovipositorial and tarsal sensilla found in this study are quite similar to those reported previously by (Cruz & Eizaguirre 2016) in Sesamia nonagrioides, Papilio hospiton (Sollai et al 2010) and Heliconius erato (Silva et al 2017). In our study, we focus on the ovipositorial and tarsal sensilla most likely involved in selection of a suitable host for oviposition.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, the sensilla, small hair like projections mainly distributed over the cuticular walls, are involved in mechanoreception and chemoreception (Carle et al 2014) located on the antennal flagellum. However several studies regarding ovipositorial and tarsal sensilla of major agricultural pests including Bactrocera dorsalis and Bactrocera diaphora (Zhang et al 2012), Sesamia nonagrioides (Cruz & Eizaguirre 2016), Spodoptera littoralis (Seada et al 2016) and Heliconius erato (Silva et al 2017) has revealed that beside olfaction it plays an important role in host and oviposition site selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations